Poverty and social impact analysis of reforms : lessons and examples from implementation - Coudouel, Aline; Dani, Anis A.; Paternostro, Stefano; World Bank. (Washington, DC : World Bank, 2006)
This book presents a collection of case studies that illustrate the spectrum of sectors and policy reforms to which PSIA can be applied; it also elaborates on the broad range of analytical tools and techniques that can be used for PSIA.
Includes bibliographical references.
osc 5/9/16. ijb 20/02/2019
Loans
Keywords: Poverty; Economic policy; Developing countries